MENINGKATKAN KEMAMPUAN DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE JARIMATIKA DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS III SD NEGERI SONTOI - Mikhael Kolo (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
Mathematics, especially in arithmetic, is a teaching of the Jarimatika technique. The finger counting method aims to assist students in operating arithmetic, especially in calculating addition and subtraction. The problems faced by teachers and students affect the low student learning outcomes. As is the case at SDN Sontoi, namely: students pay little attention to the teacher's explanation, many students talk about things outside the material, there are still students who imitate the results of other friends when working on them. Based on this analysis, the researcher will present the learning outcomes of class students at SDN Sontoi, Central Bikomi District, starting from exposure before the cycle or up to exposure to cycle I data. Based on observations of pre-cycle learning outcomes conducted by researchers, the class average is 61.6 with complete classical learning is only 61.6% This illustrates that students' learning outcomes in mathematics are still low. This is due to the use of inappropriate learning models. Teacher-centered learning activities, so students are less active in learning activities. In the first cycle of learning mathematics through the application of the jarimatics method the teacher has carried out well. This can be seen from student learning activities, learning outcomes, and in the implementation of learning that has been going according to plan. Thus the use of the jarimatics method can improve numeracy skills and student learning outcomes. Based on the results of the classroom action research that has been carried out, it can be concluded that the application of the jarimatics method can improve the results of learning mathematics on the subject of addition and subtraction of numbers for class III students at SDN Sontoi, Central Bikomi sub-district. This is indicated by an increase in the class average score, namely during pre-cycle 61.6 to 81.8 in cycle I. The application of the use of the jarimatics method succeeded in increasing mastery of the material and student learning outcomes in learning mathematics. Key Words : Jarimatika, Mathematics, Student ability